Rights for victims of crime : rebalancing justice - Waller, Irvin (Lanham, Md. : Rowman & Littlefield Publishers, 2011)
Criticizes the balance of justice in the American justice system, discussing the rights and implementation of the rights granted to victims of crime, and describing ways to improve the system and better support victims with assistance, compensation, and protection from the accused.
"When the victims of injustice lose faith in their justice system, the crime they've endured cuts only deeper, adding insult to injury. The time has come to face the truth that most victims of crime will not have their needs met and often won't experience our systems of justice as just. This short book makes its readers experts in advocating rights for victims of crime. It empowers taxpayers, voters and (potential) victims of crime to make the case to rebalance justice and support victims. Written for the millions of victims of crime and their friends and families, it helps to transform an antiquated system of criminal and civil justice into a modern system that is just and fair, shifting from neglect to respect and support. While some laws in the USA and elsewhere do support victims by providing assistance, compensation, and protection from the accused, this book also sheds a harsh light upon their inadequate implementation. Police services must catch crooks but make victims their client. Courts must balance rights for defendants and victims. Services for women, children and elderly victims must be adequately funded. Restitution from offenders must be ordered and collected, not overlooked. Fair compensation from the state must change from a secret to a given. The prevention of victimization must be the budget priority not mass incarceration. Despite the speeches and the United Nations norms, governments still leave most victims of crime without basic information, support, and assistance, let alone respect and remedies in courts. If you are not yet one of those victims of crime, social responsibility requires you to ensure that your country's systems of justice are fair to those who are and for them, this book provides an answer"--Provided by publisher.
Reinvigorating the victims' rights movement -- Forgotten but still here : what about victims of crime? -- Inalienable rights for victims : Europe and North America proclaim, Japan delivers -- First in aid : victims at the zenith of law enforcement -- Caring for victims : support, mental health, and assistance -- Making good the loss : reparation from offender, state and civil suits -- Staking claims : victims represented and heard -- Stopping crime : victimization prevention as return on investment -- The action plan : investment to rebalance justice for crime victims.
Includes bibliographical references (pages 185-195) and index.
Keywords: Victims of crimes -- Civil rights; Victims of crimes -- Government policy